2007
DOI: 10.1111/j.1530-0277.2007.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

l‐Buthionine (S,R) Sulfoximine Depletes Hepatic Glutathione But Protects Against Ethanol‐Induced Liver Injury

Abstract: L-Buthionine (S,R) sulfoximine, administered with ethanol, significantly depleted hepatic glutathione, compared with controls. However, despite the decrease in hepatic antioxidant levels, liver injury by ethanol was alleviated, due, in part, to a BSO-elicited acceleration of ethanol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…Besides inhibiting GCL, BSO accelerates Cyp2e1-dependent metabolism (8). Cyp2e1 oxidizes acetaminophen to its active metabolite, N-acetyl-p-benzoquinoneimine, which is cytotoxic due to DNA and protein adduct formation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides inhibiting GCL, BSO accelerates Cyp2e1-dependent metabolism (8). Cyp2e1 oxidizes acetaminophen to its active metabolite, N-acetyl-p-benzoquinoneimine, which is cytotoxic due to DNA and protein adduct formation.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have revealed that proteasome activity declines in animals that have higher (i.e. > 40 mmol/L) serum ethanol concentrations [40] . The lysosomal system, on the other hand, appears to be impaired by lower serum ethanol levels, as recently reported in livers of female ethanol-fed rats [41] .…”
Section: Suppression Of Autophagymentioning
confidence: 99%
“…Both serum ethanol levels (11 mg ⁄ dl in wild type and 36 mg ⁄ dl in SOD null) were well below the legally intoxicating level (80 mg ⁄ dl) in humans. This was largely because the highest level of ethanol in the diet was about 32% lower than that given to mice in a previous study (Donohue et al, 2007b). Ethanol administration caused a 3-to 3.5-fold increase in serum ALT levels in SOD ) ⁄ ) mice compared with their pair-fed controls and with wild-type ethanol-fed mice (Fig.…”
Section: Indicators Of Intoxication Ethanol Metabolism and Liver Damentioning
confidence: 75%
“…In this study, the final concentration of total ethanol calories was 20%. This was less than the 29.2.% we previously gave to ethanol-fed C57B1 ⁄ 6 mice (Donohue et al, 2007b) because we anticipated that SOD null mice would have enhanced sensitivity to oxidative stress, as reported previously (Kessova and Cederbaum, 2007) and we wanted to avoid mortality in these animals. We anticipated that, compared with wild-type animals, ethanol feeding, which itself enhances oxidative stress in wild-type animals would exacerbate hepatic protein modification, cause a rise in lysosomal leakage, and decrease proteasome activity in SOD null mice, even at the rather low levels of dietary ethanol used here.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation